An investigation of tap water quality in Kuantan, Pahang, Malaysia - Salah, HO; Sujaul, IM; Karim, Md Abdul; Nasir, MH Mohd; Abdalmnam, A; Faizal, CKM (Bangladesh Journal of Botany, 2020)
Assessment of the quality of tap water at Kuantan area of Pahang, Malaysia was investigated. The parameters analyzed were total coliform, Escherichia coli, pH, total hardness, sulfate, and selected heavy metal based on drinking water quality standard Malaysia and WHO. The results showed that the fungi in the tap water in Kuantan area in different concentrations were Aspergillus sp., Rhodotorula mucilaginosa, Penicillium citrinum, Cladosporium cladosporioides, Cerrena sp., Aspergillus aculeatus, A. flavus, Cryptococcus sp., Cladosporium perangustum, Purpureocillium lilacinum and Candida catenulata. The residual free chlorine varied from 0.05 to 1.97 mg/l.